KAJIAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KABUPATEN MINAHASA UTARA - Kevin John Manoppo; Benu Olfie L. S; Lyndon ., Pangemanan (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the size of the contribution to the agricultural sector and to determine whether the agricultural sector became the basic sector and any agricultural sub-sector that became the base sector. The data used were collected from Central Bureau of Statistics of North Minahasa District, Central Statistics Agency of North Sulawesi, North Minahasa BAPPEDA. The data is then analyzed by calculating how much the contribution of agriculture sector to the economi of North Minahasa District, LQ, and economic growth rate. The results showed that the contribution of the agricultural sector tends to decrease in the period 2010-2015, but the agricultural sector is still the sector that has the largest contribution in PDRB Kabupaten Minahasa Utara. Average growth rate of agriculture sector during the period of 2010-2015 was amounted to 4.48% the calculation of LQ indicates that the agricultural sector was still the base sector in North Minahasa Regency and agriculture sub-sector which is the base sub-sector was horticulture and the others, annual plantation sector such as the livestock sub sector and fishery sub-sector.